Long‐term outcome of infliximab treatment in chronic active ulcerative colitis: a Swedish multicentre study of 250 patients. Issue 4 (27th December 2016) - Angelison, L.; Almer, S.; Eriksson, A.; Karling, P.; Fagerberg, U.; Halfvarson, J.; Thörn, M.; Björk, J.; Hindorf, U.; Löfberg, R.; Bajor, A.; Hjortswang, H.; et al.
Summary: Background: Real‐life long‐term data on infliximab treatment in ulcerative colitis are limited. Aim: To study the long‐term efficacy and safety of infliximab in chronic active ulcerative colitis and possible predictors of colectomy and response were also examined. Methods: A retrospective multi‐centre study of infliximab treatment in 250 patients with chronic active ulcerative colitis with inclusion criteria: age ≥18 years, ambulatory treated, steroid‐dependent or intolerant and/or immunomodulator refractory or intolerant. Results: Steroid‐free clinical remission was achieved by 123/250 patients (49.2%) at 12 months and in 126/250 patients at a median follow‐up of 2.9 years (50.4%). Primary response at 3 months was achieved by 190/250 (76.0%) patients and associated with a high probability of response 168/190 (88.4%) at 12 months and 143/190 (75.3%) at follow‐up. Long‐term rate of colectomy in primary responders was 6/190 (3.2%) at 12 months and 27/190 (14.2%) at last follow‐up. Failure to achieve response at 3 months was associated with a high risk of subsequent colectomy, 29/60 (48.3%) at 12 months and 41/60 (68.3%) at follow‐up. Response at 12 months was associated with a low risk of subsequent colectomy, 14/181 (7.7%) compared with non‐response 19/34 (55.9%) ( P < 0.0001). Non‐response at 3 months was an independent predictor of subsequent colectomy (HR = 9.40, 95% CI = 5.10–17.35, P < 0.001). Concomitant azathioprine therapy did not influence outcome in terms of colectomy. Conclusions: Long‐term efficacy of infliximab treatment in chronic active ulcerative colitis is excellent especially in patients who respond to induction treatment. Conversely, non‐response at 3 months predicts a poor outcome, with a high risk of subsequent colectomy. Abstract : Linked Content This article is linked to Kilincalp et al and Angelison et al papers. To view these articles visithttps://doi.org/10.1111/apt.13993 andhttps://doi.org/10.1111/apt.14003 .